Selection of lactic acid bacteria as a probiotic and evaluated its performance on gnotobiotic catfish Clarias sp. - Enita Romasni Turnip; Widanarni, Widanarni; Anja Meryandini (Jurnal Akuakultur Indonesia)
ABSTRACT